Economic evaluation of a wind and solar energy hybrid electric sightseeing boat in Laemsak, Krabi Province, Thailand - Permzup, Chanrit; Luengchavanon, Montri; Chaiyakot, Prachyakorn (Edelweiss Applied Science and Technology, 2024)
This research aims to analyze the economic evaluation of using hybrid wind and solar energy with a diesel-engine long-tail boat in the Laemsak tourism community, Krabi province, Thailand. It is a quantitative research study that collects and estimates the costs and expenses of developing hybrid wind turbine and solar panels with diesel-engine long-tail boat, including initial development costs, operational and maintenance costs, and depreciation costs, and also estimates the benefits of using the developed boat, such as revenue from boat services, fuel savings, and carbon offset savings. The economic feasibility is analyzed using the Cost-Benefit Analysis (CBA) method by calculating the Payback Period (PP), Net Present Value (NPV), Benefit Cost Ratio (BCR), and Internal Rate of Return (IRR), as well as analyzing the Sensitivity of some uncertain factors. The analysis of the project over a 10-year period indicates PP of approximately 3-4 years, positive NPV, BCR greater than 1.0, and IRR much higher than the Interest Rate. These figures demonstrate that the project is highly economically viable and suitable for investment.